امجداسلام امجد کا حمدیہ اور نعتیہ اسلوب:"اسباب" کا خصوصی مطالعہ: A Study of Amjad Islam Amjad's Ḥamdiya and Naʻtiya Style adopted in “Asbāb” (Al-Qamar, 2023)
Amjad Islam Amjad He (1944-2023) the recipient of Presidential Award for Best Performance, Sitara-e- Imtiaz and numerous domestic and foreign awards, was not only a versatile creator but also a very reliable reference in Pakistani Urdu literature. As a poet, play writer, travel writer, columnist, critic and translator, his literary services are unforgettable. In 2019, he was awarded the highest national literary award by the President of Turkey, Tayyip Erdogan. The main reference of his literary personality is poetry. He developed Urdu ghazal and poetry. In the same way, he achieved a prominent position among contemporary writers by presenting Hamd and Naʻat in the form of ghazal and poem. In this research article, an analytical study of his Hamdiya and Naʻtiya style adopted in “Asbāb” has been discussed.
Keywords: Amjad Islam Amjad; Lahore; play writer; Urdu poet; Hamd, Naʻat; “Asbāb”